Planning for the Total Cost of Edtech Initiatives - edWeb (edWeb, 2019)
Strategic planning for edtech is an endless journey—and not just because of constantly evolving hardware and software. Upgrading infrastructure, device maintenance, and ongoing professional development, in addition to program and device costs, mean tech initiatives need permanent budget lines that take into account the total cost. In the edWebinar, “Strategic Technology Planning and Investment,” which is part of CoSN’s Empowered Superintendent series for edWeb, three superintendents who’ve been in the trenches for all aspects of district edtech plans discussed effective financial planning for technology.
KerkoCite.ItemAlsoKnownAs: 2339240:M3CJMVFE 2405685:D6RP9ZAL

The True Cost of Freemiums in Edtech - Levine, Elliott (EdTech Digest, 2019)
An industry veteran has some on-point advice about what you pay for and what you get. GUEST COLUMN | by Elliott Levine They say, “the best things in life are free,” but that is not always the case. With education technology (edtech), sometimes the cost of “free” ends up being unreasonably high in the long […]
KerkoCite.ItemAlsoKnownAs: 2339240:I9AWBSIU 2405685:SXL6X7IC

Capturing Cost Data - World Bank; International Rescue Committee (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:IJ5E95SQ 2405685:4DU2PHIC 2405685:ZSZN39Y5
Keywords: ⛔ No DOI found

One step at a time: the effects of an early literacy text-messaging program for parents of preschoolers - York, Benjamin N.; Loeb, Susanna; Doss, Christopher (Journal of Human Resources, 2019)
Large systematic differences in young children’s home learning experiences have long-term economic consequences. Many parenting programs place significant demands on parents’ time and inundate parents with information. This study evaluates the effects of READY4K!, an eight-month-long text-messaging intervention for parents of preschoolers that targets the behavioral barriers to engaged parenting. We find that READY4K! increased parental involvement at home and school by 0.15 to 0.29 standard deviations, leading to child gains in early literacy of about 0.11 standard deviations. The results point to the salience of behavioral barriers to parenting and the potential for low-cost interventions to reduce these barriers.
Publisher: University of Wisconsin Press KerkoCite.ItemAlsoKnownAs: 10.3368/jhr.54.3.0517-8756R 2405685:UV7WIAIX
Keywords: C93; D91; I21

How ed-tech can help leapfrog progress in education - Vegas, Emiliana; Ziegler, Lauren; Zerbino, Nicolas (Brookings, 2019)
This brief analyzes the use of ed-tech innovations around the world.
KerkoCite.ItemAlsoKnownAs: 2339240:LH87HU6C 2405685:D9VNFXR8

Scaling Access & Impact: Realizing the Power of EdTech - Pouezevara, Sarah; Valdivia, Ignacio Jara; Michalec, Mike; Amalia, Talitha; Fleischmann, Sybille (Omidyar Network, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GZZQHMNZ 2405685:CAXD8U9H

Does Education Need a QALY and Is LAYS It? - Crawfurd, Lee; Hares, Susannah; Le Nestour, Alexis; Rossiter, Jack (Center For Global Development, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HEH7E87J 2405685:YR4DSMZM

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CV6J6IEN 2405685:Q6H4DRVL

How solar mini-grids can bring cheap, green electricity to rural Africa - Zajicek, Charlie (odi.org, 2019)
Well-suited to small, remote communities, renewable energy mini-grids can be the most cost-effective option for rural electrification in Africa.
KerkoCite.ItemAlsoKnownAs: 2405685:4VUP32WG 2534378:IT6G3AEW

Early Grade Reading Study II (EGRS II) - USAID (2019)
The activity team works in partnership with the Department of Basic Education to evaluate the efficacy and cost-effectiveness of interventions focused on improving the performance of grade 1 and 2 learners in the subject English First Additional Language.
Library Catalog: www.edu-links.org KerkoCite.ItemAlsoKnownAs: 2405685:FPWA6KU3

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Beyond the Basics: Improving Post-Primary Content Delivery through Classroom Technology - Beg, Sabrin A; Lucas, Adrienne M; Halim, Waqas; Saif, Umar (National Bureau of Economic Research, 2019)
Using an RCT in middle schools in Pakistan, we test the effect of a government- implemented in-class technology and brief teacher training intervention on student achievement in grade level mathematics and science. After only 4 months of exposure, student's combined math and science score increased by 0.3 standard deviations on both project and government tests, 59 percent more than the control group. Students were also more likely to pass the provincial high-stakes exams. Increased attendance by both students and teachers indicate technology can increase other inputs. At the 200 school scale, this program is extremely cost-effective.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w25704 2339240:8S5BZEQ5 2339240:N3IQ9VDH 2405685:56WJPPUE 2405685:MXHG8QD6
Keywords: EXCLUSION CRITERIA APPLIED; Quality: H; Relevance: M

How behavioral science can empower parents to improve children's educational outcomes - Bergman, Peter (Behavioral Science & Policy, 2019)
Parents powerfully influence their children’s educational outcomes. Yet psychological and informational barriers impede parents’ ability to engage with their children in ways that improve outcomes: parents tend to have inflated perceptions of their children’s performance, which can deter them from taking helpful steps to effectively support their learning, and parenting is complex. Limited cognitive bandwidth for coping with complexities can steer parents’ attention away from actions that have long-term benefits for their children and toward actions yielding immediate returns. Poor school-to-parent communication and poverty exacerbate all of these problems. In this article, the author demonstrates how providing timely, actionable information to parents can lower these barriers and help parents engage with their children more productively from kindergarten through high school. Moreover, providing this information can improve educational outcomes at low cost.
KerkoCite.ItemAlsoKnownAs: 10.1353/bsp.2019.0004 2339240:EFP32JJ7 2405685:W5PIX5JE

Disrupting education? Experimental evidence on technology-aided instruction in India - Muralidharan, Karthik; Singh, Abhijeet; Ganimian, Alejandro J. (American Economic Review, 2019)
We study the impact of a personalized technology-aided after-school instruction program in middle-school grades in urban India using a lottery that provided winners with free access to the program. Lottery winners scored 0.37 sigma higher in math and 0.23 sigma higher in Hindi over just a 4.5-month period. IV estimates suggest that attending the program for 90 days would increase math and Hindi test scores by 0.6 sigma and 0.39 sigma respectively. We find similar absolute test score gains for all students, but much greater relative gains for academically-weaker students. Our results suggest that well-designed, technology-aided instruction programs can sharply improve productivity in delivering education.
shortDOI: 10/ggqfkz KerkoCite.ItemAlsoKnownAs: 10.1257/aer.20171112 10/ggqfkz 2339240:2URYXAL4 2339240:4YAVCBCF 2339240:7V3XB7ZJ 2339240:8LAH5EZS 2339240:FPI5PFGU 2339240:QRHQXRYZ 2339240:U2V8LTLL 2339240:V85IRLNH 2405685:7WM44UJQ 2405685:AJVTKPNE 2405685:EKZSBGYG 2405685:EWWJF7S6 2405685:EZDRM9UV 2405685:HDWKAHGN 2405685:MADAMGDT 2405685:N2HAMNQ9 2405685:SYASQJ2L 2405685:YFXKBCTF 2534378:JMN7CGMF
Keywords: Analysis of Education; Returns to Education; Education: Government Policy; Human Capital; Human Development; Income Distribution; Labor Productivity; Economic Development: Human Resources; Migration; Occupational Choice; Quality: H; Relevance: H; Skills; _THEME: Teacher Professional Development; ___working_potential_duplicate; ⛔ No DOI found

Cloud computing architecture for eLearning in secondary schools - Mwakisole, Kennedy; Kissaka, Mussa; Mtebe, Joel (The African Journal of Information Systems, 2019)
In recent years, schools have been investing heavily on information and communications technology (ICT) infrastructure to implement eLearning systems to enhance the quality of education in secondary schools in Tanzania. The majority of these systems are implemented using a traditional web-based eLearning approach on school premises which is costly and limits usage due to lack of scalability and flexibility. Consequently, many schools have started adopting cloud computing as a solution. However, this adaption depends on well-defined cloud eLearning architecture. This study proposed cloud architecture for implementing an eLearning system in secondary schools in Tanzania by adopting various layers proposed in previous studies. The effectiveness of this proposal was evaluated by comparing its performance with a similar traditional web-based eLearning system using the Moodle benchmark tool and Apache Jmeter. The study found that eLearning systems implemented in the cloud-based infrastructure had better performance metrics than web-based eLearning systems on school premises.
KerkoCite.ItemAlsoKnownAs: 2339240:H37DIS7E 2405685:QILWRT8Y
Keywords: ⛔ No DOI found

Challenge and srivers of over-Enrollment in the early years of primary school in Uganda - Weatherholt, Tara; Jordan, Rachel; Crouch, Luis; Barnett, Ed; Pressley, Jennifer (International Journal of Early Childhood, 2019)
Consistent over-enrollment, together with low official repetition rates, in the early years of school indicates inaccurate reporting of repetition, which may mask the reasons for low primary school completion. Actual repetition rates may be higher and pose issues for teachers through overcrowding of classrooms and issues for governments through inefficient education systems. This research explores repetition rates of students in Primary 1 in Uganda and considers the implications for efficiency and quality of education for the early years of school. The sample comprised 1440 students in Primary 1 classrooms in 120 schools. Interviews were conducted with 1318 caregivers of randomly selected students and 1439 teachers of the same students, and official records from 118 schools were examined to compare age and repetition rates. Findings showed that caregiver- and teacher-reported repetition is much higher than officially reported by schools; that repetition is strongly linked to non-attendance in pre-primary schooling; and that caregivers reported more over-age students, fewer target-age students, and more under-age students than official school records. Policy implications include the need for dialogue around repetition rates and the possible efficiency effects of less-costly, pre-primary education on the total primary schooling cycle.
KerkoCite.ItemAlsoKnownAs: 10.1007/s13158-019-00238-3 2339240:3WMYLF8F 2405685:975JWM6R 4656463:2HX448CB
Keywords: Early childhood; Education efficiency; Low-income countries; Pre-primary education; Repetition

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Digital literacy for children — 10 things to know - UNICEF (2019)
Digital literacy goes beyond technical know-how. It refers to the knowledge, skills and attitudes that allow children to be both safe and empowered in an increasingly digital world. This encompasses their play, participation, socializing, searching and learning through digital technologies. What constitutes digital literacy will vary according to children’s age, local culture and context. Children need to be digitally literate even when they are not online. Facial scanning and artificial intelligence-based profiling increasingly affect children’s lives. Children’s schooling, social welfare and future job opportunities may depend on how well they understand the digital world around them. Digital literacy is a growing part of any approach to skills development. It features in UNICEF’s framework which seeks to prepare children and adolescents for school, work and life. In addition to digital literacy, other interconnected skills for UNICEF are: foundational skills (literacy and numeracy); transferable skills (also known as life skills, 21st-century skills or soft skills); and job-specific skills (technical and vocational skills). Tools to develop and assess digital literacy are proliferating. A number of digital competence frameworks have been developed by both international agencies and companies. Frameworks are a necessary starting point as they define the boundaries of what constitutes digital literacy and inform curricula and assessments. Despite using a range of labels (e.g. digital literacy, skills, citizenship), they broadly converge around the idea of a set of competencies that include technical as well as transferable skills, such as communication and problem solving. Yet most existing tools place little emphasis on children. Digital literacy definitions usually focus on citizens of all ages and not on children specifically. UNICEF believes there is a need to focus more on digital literacy for children, who have unique needs. In this area, there is a slow change from a risk and safety paradigm towards rights-based approaches that favour expression, play and development. Few programmes operate at scale or have been evaluated for impact. One contributing factor is the lack of global consensus and standards that makes it difficult for governments and other stakeholders to design and implement comparative and cost-effective initiatives, especially within developing countries. Similarly, UNICEF programmes would benefit from greater coordination. While UNICEF has delivered a range of digital literacy programmes at the request of governments, a survey of 40 initiatives carried out by 37 Country Offices shows they are not well coordinated with each other, and knowledge is not systematically generated or shared about efficacy and impact. Implementing digital literacy is not easy. According to the Country Offices surveyed, key barriers to digital literacy programming are: lack of teachers’ and trainers’ capacity; lack of ICT infrastructure; low connectivity (especially for remote areas); and a lack of understanding from decision-makers. The Country Offices are asking for policy development support, digital literacy frameworks, curriculum guidelines and practical tools, such as training manuals and toolkits. Some existing digital literacy frameworks or tools suit UNICEF well. These include the DigComp framework of the European Commission and the Digital Kids Asia-Pacific framework developed by the UNESCO Asia and Pacific Regional Office in Bangkok. If using existing digital literacy frameworks, UNICEF can add value by focusing on children. Digital literacy programmes should be context-driven. Implementing digital literacy programmes effectively requires more than simply importing a good programme from elsewhere. Beyond choosing a framework, an integrated approach to digital literacy involves undertaking a preliminary diagnostic review of the local context, developing operationalization guidelines and conducting impact assessments.
KerkoCite.ItemAlsoKnownAs: 2339240:DAVC5T72 2405685:LGV5JGFE